2010
DOI: 10.1007/s13105-010-0021-y
|View full text |Cite
|
Sign up to set email alerts
|

Tempol protects the gallbladder against ischemia/reperfusion

Abstract: Impairment in gallbladder emptying, increase in residual volume, and reduced smooth muscle contractility are hallmarks of acute acalculous cholecystitis and seem to be related to ischemia/reperfusion (I/R). This study was designed to determine the effects of tempol, a general antioxidant, on I/R-induced changes in gallbladder contractile capacity, the mechanisms involved in the contractile process, and the level of inflammatory mediators. Experimental gallbladder I/R was induced in male guinea pigs by common b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…TEMPOL has been shown to reduce post-ischemic inflammatory signaling in a rat [54] and mouse [57] model of renal I/R and a Guinea pig model of gallbladder I/R [56]. Oxidative stress and cell death during I/R lead to highly pleiotropic immune signaling and sterile inflammation [9], which was confirmed in our model on the basis of the IL-6 ( Figure 3B) and MPO data ( Figure 3G, H).…”
Section: Tempol Reduces Peritubular and Glomerular Neutrophil Influx supporting
confidence: 79%
See 1 more Smart Citation
“…TEMPOL has been shown to reduce post-ischemic inflammatory signaling in a rat [54] and mouse [57] model of renal I/R and a Guinea pig model of gallbladder I/R [56]. Oxidative stress and cell death during I/R lead to highly pleiotropic immune signaling and sterile inflammation [9], which was confirmed in our model on the basis of the IL-6 ( Figure 3B) and MPO data ( Figure 3G, H).…”
Section: Tempol Reduces Peritubular and Glomerular Neutrophil Influx supporting
confidence: 79%
“…Accordingly, numerous studies have shown that TEMPOL reduces I/R AKI in different species, including rats [54]. The antioxidant [55], immunosuppressive [56,57], and AKIameliorating effects of TEMPOL are well-established in I/R AKI. Conversely, relatively little information is available in terms of renal oxygenation, which is critical for renal function [8].…”
Section: Introductionmentioning
confidence: 99%
“…Acute acalculous cholecystitis (AC) is characterized by gallbladder inflammation without evidence of calculi or sludge [1]. Bile stasis, ischemia-reperfusion injury, and systemic inflammatory response syndrome (SIRS) have been suggested as pathogenic factors [2].…”
Section: Introductionmentioning
confidence: 99%
“…Bile stasis, ischemia-reperfusion injury, and systemic inflammatory response syndrome (SIRS) have been suggested as pathogenic factors [2]. In critically ill patients, AC is believed to have a more fulminant course, and is associated with significantly higher morbidity and mortality than gallstone-associated acute cholecystitis [1]. Common bile duct ligation (CBDL) in the guinea pig produces a histologic picture that is nearly identical to that of acute human cholecystitis, with subserosal edema, hemorrhage, white blood cell infiltration, and vasodilation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative AAC was unrelated to the biliary tract, which was characterized by gallbladder inflammation without evidence of calculi or sludge [8]. …”
mentioning
confidence: 99%